Sinergi Care, Capability, Opportunity Sebagai Kunci Sukses Pengembangan Diri Siswa SMA Mathlaul Anwar - Sumitra, Agus; Syafa’at, Siti; Adhi Purwaningrum, Fajar; Uke Saraswati, Ririn; Yulia Aryanto, Intan; Yayat Hidayat, Asep; Baehaki, Ahmad; Iqbal Fauzi, Muhamad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The community service activity entitled Synergy of Care, Capability, Opportunity as the Key to Successful Self-Development for Mathlaul Anwa Batujaya High School Students aims to improve the quality of student self-development through a holistic approach with three key elements: care, capability, and opportunity, which play an important role in supporting students' personal growth. The method used was a seminar. The activity was attended by 48 participants consisting of 40 XII grade students of Mathlaul Anwar High School and 8 general participants. Based on the indicator survey before the activity only 11% of participants understood the importance of self-development through care, capability and opportunity. After the activity 100% of participants stated that they understood it. Through this activity, it is hoped that Mathlaul Anwar Batujaya High School students can develop themselves optimally and be ready to face future challenges. The outputs of this activity include increasing participants' skills, increasing self-confidence, and participants being able to explore their potential.